Tobat Sebagai Sebuah Terapi (Kajian Psikoterapi Islam) - Erba Rozalina Yulianti (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2017)
This paper will discuss how the concept of repentance ( tobat) in Islam can be used as therapy for human souls who are mired in a life of vice and sin. Either a sin will be cause a negative behaviour or negative thought. It is obvious that when someone is doing a lot of sin, so all the thoughts, feelings and behaviors are getting disorder. Based on this effect a sin will disturb the balance of man thinking, feeling and behavior. So it may not find tranquility and peace of mind. Indeed, it appears the anxiety and restlessness that lead to the emergence of a more severe psychological symptoms. Tobat which has a combination of psychological functions can fill the rest of Islamic Psychoterapy. This is understandable because Tobat process has formed as a variety of positive psycholocical functioning. They are: 1) Awareness to change behavior, 2) Self evaluation ( comfession), 3) Positve feelings ( remorse ), 4). Positive attitudes ( commitment), 5). Change of behavior consitently.